Il ponte sobre o Tejo: metafora di un Portogallo in transizione - Gori, Annarita (2019)
On August 6th 1966 the Ponte sobre o Tejo was inaugurated. It was the biggest European suspension bridge ever built. Roger Blought, president of the construction firm – the United States Steel Company – defined it as an “iconic structure” for the city such as the Eiffel Tower in Paris or the Statue of Liberty in New York. The symbolic power of the bridge is well demonstrated by the several changes of its name: Ponte sobre o Tejo the official denomination; Salazar Bridge in 1966 and 25th of April Bridge in 1974 after the carnation revolution. Nevertheless restricting the study of this infrastructure only to its iconic dimension would be simplistic. This article, through the analysis of archive documents and newspapers, aims to investigate the bridge as a key to read some aspects of Contemporary Portugal paying particular attention to the period between the 1950s and 1960s: national economic and technological development, urban and demographic changes, and international relationships.